SOCIAL CARE DEVELOPMENT: THE ROLE OF COMMUNITY-BASED PROJECT (CBP) OF GIBS JUNIOR HIGH SCHOOL IN STUDENT CHARACTER BUILDING - Nur'aini, Fatwa; Ramadhan, M. Adhitya; Mutiani, Mutiani; Jumriani, Jumriani; Abbas, Ersis Warmansyah (International Conference On Social Science Education, 2024)
Community-Based Project (CBP) at SMP Global Islamic Boarding School (GIBS) is an organization that aims to shape the character of students so that they have social awareness and an awareness of their role in society. This study uses a case study approach with qualitative methods, involving observation techniques, interviews, and document analysis. The results of the study indicate that the implementation of CBP at SMP Global Islamic Boarding School (GIBS) has a positive impact on the development of student character. Those involved in this program experienced an increase in social awareness, communication skills, and problem-solving abilities. In addition, CBP also helps students understand the importance of active participation in society and responsibility for their surroundings. The results of the study indicate that the Community-Based Project (CBP) organization at SMP Global Islamic Boarding School (GIBS) has succeeded in developing empathy, communication, and problem-solving abilities in students. This program encourages students to interact with the community, increases social awareness, and equips them with practical skills that are useful for everyday life